ANALISIS PERAWATAN TALI PUSAT DENGAN ASI TERHADAP LAMANYA WAKTU PELEPASAN TALI PUSAT - Romlah; Iltru Misdeti; Novita Anggraini (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2018)
According to the Ministry of Health of the Republic of Indonesia (2008, in Eprila, et al, 2015) neonatal deaths due to infection amounted to 57.1% including cord infections namely tetanus neonaturum by 9.5%. Infection of the umbilical cord can cause tetanus neonatorum in infants, the main cause of tetanus neonatrum because of poor cord care, the umbilical cord is the entry point for bacteria to the baby, Colistridium tetanus bacteria (Anwar S, 2008 in Eprilia, et al, 2015).This study aimed to analyze umbilical cord care with breast milk for the length of time of umbilical cord release. This type of quantitative research with a descriptive survey approach to assess the length of time for umbilical cord release in infants who received umbilical cord care using breast milk. The population in this study all newborns in the Mandiri Practice Midwife Look at the Basuki Rahmat Health Center in Palembang. The number of samples in this study 78 respondents. Sampling technique with purposive sampling. Data analysis technique uses univariate analysis.The results of univariateanalysis showed results based on maternal age from the number of 78 mothers with the highest age, namely 21-34 years (96.2%). Based on the gestational age of the number of 78 mothers with the highest gestational age of 37-42 years (100%). Based on the parity of the number of 78 mothers of infants with the highest parity of the second or more (67.9%). Based on birth weight from the number of 78 babies with the highest birth weight 2500-<4000 grams (100%). Based on gender, there were 78 babies with more women (52.6%). Based on the time span of umbilical cord release from the number of 78 infants with the most <5 days (78.2%). Based on the average umbilical cord release from the number of 78 babies with an average umbilical cord release 3.71 days with the fastest time of 2 days and the longest 7 days. Based on the results of the study, it was suggested for BPM Nurtilah to be a fixed procedure (PROTAp) for cord care in newborns and neonates for nursing care in infants